Gay Glass Ceilings: Sexual Orientation and Workplace Authority in the UK - Cevat Giray Aksoy; Christopher S. Carpenter; Jeff Frank; Matt L. Huffman (Institute of Labor Economics (IZA), 2018)
A burgeoning literature has examined earnings inequalities associated with a minority sexual orientation, but far less is known about sexual orientation-based differences in access to workplace authority – in contrast to well-documented gender and race-specific differences. We provide the first large-scale evidence on this question using confidential data from the 2009-2014 UK Integrated Household Surveys (IHS) (N = 607,709). We are the first to document that gay men and lesbians are significantly more likely to have objective measures of workplace authority compared to otherwise similar heterosexual men and women. However, we also find clear evidence that gay men face glass ceilings: their higher likelihood of attaining workplace authority is driven entirely by their significantly higher odds of being low-level managers. In fact, gay men are significantly less likely than comparable heterosexual men to be in the highest-level managerial positions that come with higher status and pay. Oaxaca decompositions suggest that this differential access to workplace authority for gay men is due to discrimination as opposed to different skills and characteristics. Moreover, this "gay glass ceiling" is stronger for racial minorities than for whites. Corresponding effects for lesbians exist but are notably weaker. These results provide the first direct evidence of social stratification in the workplace associated with a minority sexual orientation and reveal that differences are exacerbated for individuals with multiple marginalized identities.
Keywords: J15; J71; M54; 330; sexual orientation; workplace authority; supervisory authority; managerial occupations